Integrating Green Chemistry Principles into Chemistry Education for Achieving Sustainable Development Goals (SDGs): A Systematic Literature - Tri Diana Alfiyanti Puspita; Muntholib; Ridwan Joharmawan (Postgraduate, University of Mataram, 2026)
Advances in science and technology increase chemical use, raising environmental and health concerns. Consequently, green chemistry has emerged to promote sustainable learning practices. This Systematic Literature Review (SLR) aims to analyze the implementation of green chemistry principles in chemistry education using the PRISMA framework. Data were retrieved from Scopus (via Publish or Perish), ACS Publications, and ERIC for the period from January 2016 up to January 2026. Of the 12,737 total articles retrieved, 57 met the inclusion criteria for final analysis. The results indicate that the most frequently implemented green chemistry principle is prevention, followed by safer solvents and auxiliaries and renewable feedstocks, while others remain rarely implemented, highlighting a critical gap for future research and curriculum development. Implementation occurs through diverse learning activities, particularly laboratory experiments, supported by varied pedagogical models and media. Furthermore, integrating green chemistry positively impacts critical thinking, higher-order thinking, systems thinking, and sustainability awareness. Thus, green chemistry strongly supports more contextual, safer, and sustainability-oriented chemistry learning.